Common Dermatoses in Patients with Obsessive Compulsive Disorders - Mircea Tampa; Maria Isabela Sarbu; Clara Matei; Vasile Benea; Simona Roxana Georgescu (Journal of Mind and Medical Sciences)
Obsessive-compulsive disorder is a chronic, debilitating syndrome, consisting of intrusive thoughts- which are experienced as inappropriate by the patient and are producing anxiety- and compulsions, defined as repetitive behaviours produced to reduce anxiety. While patients with obsessive-compulsive disorder typically have xerosis, eczema or lichen simplex chronicus, as a result of frequent washing or rubbing their skin, several other disorders which are included in the group of factitious disorders have also been associated with obsessive-compulsive disorder. A close collaboration between the dermatologist and the psychiatrist is therefore mandatory in order to achieve favourable outcomes for these patients. The aim of the article is to present the most frequent dermatological disorders associated with obsessive-compulsive disorder and to look over some of the rare ones.